Papillary fibroelastoma of the aortic valve - Yu-Hern Tan; Chen-Yen Chien (Formosan Journal of Surgery, 2020)
Papillary fibroelastoma (PFE) is the second most common benign primary cardiac tumor. The clinical spectrum of PFE ranges widely from asymptomatic to life-threatening thromboembolic complications. We herein report a case of a 59-year-old woman presenting with an incidentally found aortic valve tumor treated with valve-sparing surgical excision. There is no guideline for the management of PFE, but surgical excision is generally suggested for left-sided PFE.